Validation of a Novel Strategy for Fluorescence Quenching for a Self-Quenching Fluorogenic Probe and Its Application for Visual Loop-Mediated Isothermal Amplification Detection During Food Safety Analysis - Sisi Huang; Shihui Wang; Tianlong Wang; Hongwei Song; Yan Guo; Xiong Xiong; Libin Wang (Foods)
The self-quenching fluorogenic probe facilitates precise identification of LAMP (loop-mediated isothermal amplification) amplicons, unaffected by non-specific products resulting from primer dimers. However, low quenching efficiency by surrounding nucleobases leads to high background signal, posing significant challenges for visual inspection with the naked eye. The present study aims to identify an oligonucleotide sequence that is complementary to the self-quenching fluorogenic probe, and to employ the fluorescence super-quenching mechanism of double-stranded DNA to establish a visualization system for the LAMP assay. The results indicated that the incorporation of a sequence fully complementary to the probe could significantly reduce the system’s background fluorescence (p < 0.05). When the melting temperature exceeds room temperature, truncating the complementary sequence from the 3′ end does not compromise the probe’s quenching efficiency. The LAMP visualization system, using a 10–13-base complementary sequence of the loop primer-based probe, could effectively minimize background fluorescence and yield straightforward visual results post-reaction. Applied to rainbow trout and Atlantic salmon detection, the system detected 1 pg DNA in a closed-tube format. In conclusion, a suitable complementary sequence can reduce the background fluorescence of the self-quenching fluorogenic probe. Employing this sequence alongside the self-quenching fluorogenic probe to develop a low-background fluorescence LAMP system demonstrates great potential for successful visual detection and holds considerable promotional merit.